Stepwise Protocols for Preparation and Use of Porcine Ear Skin for in Vitro Skin Permeation Studies Using Franz Diffusion Cells. Issue 3 (15th March 2022) - Silva, Izabela R.; Lima, Flávia A.; Reis, Eduardo C. O.; Ferreira, Lucas A. M.; Goulart, Gisele A. C.
Abstract: The skin, the largest organ of the body, is an attractive route of topical and systemic drug administration. During the development of topical formulations, in vitro skin permeation studies using biological membranes mounted in Franz diffusion cells are a useful tool to assess the permeation of substances through the skin, and are recommended by the Organization for Economic Cooperation and Development (OECD). Among the types of biological membranes used in such studies, porcine ear skin has been identified as the most promising, due to its similarities to human skin and its greater accessibility as compared to human skin. To standardize techniques for the preparation and use of porcine ear skin as biological membrane, here we present systematic procedures for the selection of porcine ears, their cleaning, the removal of skin from cartilage, its transformation into membranes, and its use for the in vitro assessment of the permeation of drugs from topical formulations. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Obtaining porcine ear membranes Basic Protocol 2 : Preparation of membranes from porcine ear skin and use of membranes for in vitro skin permeation studies